Influence of nitrogen source and sucrose concentration on inulinase production by Kluyveromyces marxianus in fed-batch fermentation - Cazetta, M. L. [UNESP]; Contiero, Jonas [UNESP] (Academic Journals, 2011)
This work studied the influence of nitrogen source and sucrose concentration in the feeding medium for biomass and inulinase production by Kluyveromyces marxianus var. bulgaricus. The results show that the best nitrogen source was a combination of 5 g/L of yeast extract and 10 g/L of peptone. Both cellular growth and enzymatic activity increased with sucrose concentration in the feeding medium (from 200 to 500 g/L). When the sucrose concentration reached 600 g/L, both cellular growth and enzymatic activity decreased.
Keywords: Kluyveromyces marxianus; nitrogen; sucrose; inulinase; fed-batch fermentation